Evaluation of the Gender, Agriculture, and Assets Project, Phase 2 gender and empowerment frameworks and tools - Johnson, Nancy L. (International Food Policy Research Institute, 2021)
Two key outputs of the Gender, Agriculture, and Assets Project, Phase 2 (GAAP2) are the project-level Women’s Empowerment in Agriculture Index (pro-WEAI) and the Reach, Benefit, Empower (RBE) framework. An e-survey was used to get a sense of awareness and use of the pro-WEAI and the RBE framework among a target population of potential users (A4NH program stakeholders). More than 30 semi-structured interviews were conducted with funders, implementers, and evaluators, mainly but not exclusively associated with GAAP2, to understand how tools were used at different stages of the program/project cycle, from influencing program objectives and outcomes to program/project design to impact evaluation. The evaluation found that even though the pro-WEAI and the RBE framework are relatively new and their use is not yet widespread, their use in projects is growing and they have contributed to changes in project priorities and in how projects seeking to empower women are designed and evaluated.